Training Program For Developing Tourism Businesses For Students At Ma Industri Al-Jabar Batam - Wahyudi Ilham (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
The Tourism Business Development Training for Students at MA Industri Al-Jabar Batam aims to provide students with essential skills and knowledge in tourism entrepreneurship. This program introduces concepts of tourism business, strategies for business growth, and current trends and innovations within the industry. Through engaging methods such as case studies, business simulations, and field activities, students are guided to explore potential business opportunities in their local communities. This training is intended to develop an entrepreneurial mindset, foster creativity and self-reliance, and prepare students to become active entrepreneurs in the tourism sector. The program's impact is expected to create graduates who are job-ready and contribute to local economic growth through tourism business initiatives.